2013
DOI: 10.9755/ejfa.v25i1.15376
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Landraces: A mini review <br>

Abstract: Traditional farmers planted diverse assemblages of wheat landraces to lower the risk of failure and increase food security because they had limited capacity to control the spatially heterogeneous and temporally unpredictable environments. This practice led to the development of landrace meta-populations of wheat and the emergence of farmers' seed systems through which they accessed and exchanged diverse genetic material. During the last ~50 years, the introduction of high-yielding wheat varieties into, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
41
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 32 publications
8
41
0
3
Order By: Relevance
“…These populations were subjected to natural, and probably man-made, selection; were not subjected to modern improvement methods; and were managed by subsistence, resource-poor farmers in a marginal zone for wheat production (Al-Maskri et al, 2003;Al-Khanjary et al, 2007;Gebaur et al, 2010). We concluded that these landrace populations, similar to other landraces in the primary (Ali Deb et al, 1992;Karagö z and Zençirçi 2005;Ahmadizadeh et al, 2011;Jaradat, 2013) and secondary (Bechere et al, 1995;1996) centers of wheat diversity, can provide a largely unexplored diversity with great potential for broadening the genetic base of modern wheat cultivars.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…These populations were subjected to natural, and probably man-made, selection; were not subjected to modern improvement methods; and were managed by subsistence, resource-poor farmers in a marginal zone for wheat production (Al-Maskri et al, 2003;Al-Khanjary et al, 2007;Gebaur et al, 2010). We concluded that these landrace populations, similar to other landraces in the primary (Ali Deb et al, 1992;Karagö z and Zençirçi 2005;Ahmadizadeh et al, 2011;Jaradat, 2013) and secondary (Bechere et al, 1995;1996) centers of wheat diversity, can provide a largely unexplored diversity with great potential for broadening the genetic base of modern wheat cultivars.…”
Section: Discussionmentioning
confidence: 61%
“…The genetic erosion caused by the displacement of wheat landraces in developing countries (Van de Wouw et al, 2009), including Oman (Guarino, 1990;Gebauer et al, 2010), is a concern for wheat breeders because these genetic resources may be the most valuable sources for broadening the genetic bases for many traits in current and future wheat breeding and improvement programs. While the problem was globally addressed, to some extent, by international strategy of collecting, conserving and utilization of wheat landraces (Bradsley and Thomas, 2005;Goats and Bockelman, 2012), specific efforts to identify potentially new genetic variability for immediate use in breeding programs are still needed at local levels, especially in the developing world (Akram et al, 2012;Ahmad et al, 2013;Jaradat, 2013). Local landraces may provide new alleles for the improvement of commercially valuable traits in wheat, including quality traits and adaptation to biotic and abiotic stresses (Yedliay et al, 2011;Goats and Bockelman, 2102).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations